Neural Activation Patterns During Emotional Working Memory Task: an fMRI Study - Alwani Mohd Asri, Nur; Fong Chan, Lai; Nazlim Yusoff, Ahmad; Leng Eu, Choon; Sharis Osman, Syazarina; Zhao, Zhiying; Xu, Xiaolei; Becker, Benjamin; Mohamad, Mazlyfarina (International Journal of Engineering and Technology, 2018)
Emotional stimuli may have positive effects in cognitive processes that allows for temporary storage and manipulation of information. However, the influence of emotional stimuli, along with its neural correlates have not been fully analysed so far. This study aimed at investigating the neural and behavioral effect that the emotional content of stimuli has on working memory performance. In this functional magnetic resonance imaging (fMRI) study, we induced different emotional faces pictures while participants (n = 17) performed an n-back visual working memory task. Data were analyzed using Statistical Parametric Mapping 12 (SPM-12). Result showed emotional working memory n-back tasks activated motor, occipital, frontal, parietal regions. Frontal and parietal regions showed more activation in 1-back task association with increased working memory load. This showed that additional component need in maintaining a representation of the previous stimuli.Â